2008
DOI: 10.1111/j.1369-7625.2008.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving informed consent: pilot of a decision aid for women invited to participate in a breast cancer prevention trial (IBIS‐II DCIS)

Abstract: Background Patients and clinicians report difficulties with the process of informed consent to clinical trials and audiotape audits show that critical information is often omitted or poorly presented. Decision aids (DAs) may assist in improving consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…This conceptualisation as a deliberate decision between healthcare options helps place the decision in the context of patients' illness management and lifestyle. Our findings add to others' evidence for trial information to be framed in the context of patients' illness management (Abhyankar et al, 2014;Brown et al, 2004;Entwistle, 2008;Gillies et al, 2014;Juraskova et al, 2008;Juraskova et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This conceptualisation as a deliberate decision between healthcare options helps place the decision in the context of patients' illness management and lifestyle. Our findings add to others' evidence for trial information to be framed in the context of patients' illness management (Abhyankar et al, 2014;Brown et al, 2004;Entwistle, 2008;Gillies et al, 2014;Juraskova et al, 2008;Juraskova et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…This could be achieved by 1) improving information in consent to help patients' active decision making between consequences of other treatment options and consequences of taking part in trial (Abhyankar et al, 2011). A decision aid (DA) developed by Juraskova et al (2008; to assist women's decision making about participation in a cancer prevention trial has shown promising results in improving understanding, reducing decisional regret and enhancing decision quality over and above the usual consent information. The DA presents an explicit choice between the trial participation and standard care options, which is a more balanced and complete presentation than the choice between 'trial' and 'no trial' (Abhyankar et al, 2013; trial is embedded appropriately in care pathway and 3) training to non-trial staff in how to provide information about the trial in the context of delivering care (Mills et al, 2014).…”
Section: Implications For Practicementioning
confidence: 99%
“…Decision aids are thought to be valuable to adult patients when making difficult treatment or screening decisions. The value of these aids in helping adult patients make decisions about clinical trials has also been reported 153 and further studies are under way in adult trials. 154 The value of decision aids for parents considering a trial for their child has not yet been investigated.…”
Section: Discussing Trials With Parentsmentioning
confidence: 99%
“…However, there is less discussion of the difficulties associated with undertaking such studies, including costs 2 , ethical problems, issues associated with informed consent 3 , problems of bias, clinician preference for certain treatment options 4 , difficulties in recruiting sufficient patients 5 and overestimating the number of patients who would be eligible for inclusion in the study or would agree to participate 6 .…”
Section: Introductionmentioning
confidence: 99%